Proximal junctional kyphosis following T10-pelvis fusion presenting with neurologic compromise: case presentations and review of the literature. (1st November 2020) - Piazza, Matthew; Sullivan, Patricia Zadnik; Madsen, Peter; Branche, Marc; McShane, Brendan; Saylany, Anissa; Sharma, Nikhil; Arlet, Vincent; Ozturk, Ali
Abstract: Purpose: Proximal Junctional Kyphosis (PJK) is a well-documented phenomenon following spinal instrumented fusion. Myelopathy associated with proximal junctional failure (PJF) is poorly described in the literature. Adjacent segment disease, fracture above the upper instrumented vertebrae and subluxation may all cause cord compression, ambulatory dysfunction, and/or lower extremity weakness in the postoperative period. Materials and methods: We review the literature on PJK and PJF, and discusses the postoperative management of three patients who experienced myelopathy associated with PJF following T9/10 to pelvis fusion at a single institution. Results and conclusions: PJF with myelopathy must be diagnosed and surgically corrected early on so as to minimize permanent neurologic injury. Patients requiring significant sagittal deformity correction are at greater risk for PJF, and may benefit from constructs terminating in the upper thoracic spine.